2011
DOI: 10.1523/jneurosci.3214-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Choice from Non-Choice: Predicting Consumer Preferences from Blood Oxygenation Level-Dependent Signals Obtained during Passive Viewing

Abstract: Decision-making is often viewed as a two-stage process, where subjective values are first assigned to each option and then the option of the highest value is selected. Converging evidence suggests that these subjective values are represented in the striatum and medial prefrontal cortex (MPFC). A separate line of evidence suggests that activation in the same areas represents the values of rewards even when choice is not required, as in classical conditioning tasks. However, it is unclear whether the same neural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
162
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 46 publications
26
162
1
1
Order By: Relevance
“…In line with this finding, activation in the VS has previously been shown to reflect preference judgment for various objects when participants actively evaluated these stimuli with respect to other, non-preference-related aspects such as roundness or age (Kim et al, 2007;Lebreton et al, 2009;Levy et al, 2011). Extending these earlier findings, the present study predicted individual preference ranks for task-irrelevant politicians from striatal activation while attention was diverted to an unrelated, ongoing task.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In line with this finding, activation in the VS has previously been shown to reflect preference judgment for various objects when participants actively evaluated these stimuli with respect to other, non-preference-related aspects such as roundness or age (Kim et al, 2007;Lebreton et al, 2009;Levy et al, 2011). Extending these earlier findings, the present study predicted individual preference ranks for task-irrelevant politicians from striatal activation while attention was diverted to an unrelated, ongoing task.…”
Section: Discussionsupporting
confidence: 84%
“…Changes of preferences were also found to be positively correlated with activation in the anterior insula and the dorsal ACC when participants made explicit preference judgments for songs (Berns et al, 2010).Moreover, activation in these brain regions has been involved in automatic valuation and preference judgments. Brain responses in the PCC and the mPFC were shown to be significantly higher for preferred stimuli compared to non-preferred stimuli even when such judgments were not required (i.e., passive viewing) or when age judgments were performed (Lebreton et al, 2009;Levy et al, 2011).…”
Section: Discussionmentioning
confidence: 98%
“…The region has been ascribed a role in attentional processes (Bisley and Goldberg, 2010), e.g. when non-food objects are viewed (Levy et al, 2011). However, the superior parietal cortex has also been reported to be involved in the abstract coding of stimulus values in order to mediate goal-directed behaviors and to maximize the outcome of choices taken (Kahnt et al, 2014), as well as to enable choices between several alternative options (Kable and Glimcher, 2009;McClure et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…When facing a choice, the economic agent is supposed to valuate the available options and then select the one with the highest expected value (Von Neumann and Morgenstern, 1944;Rangel et al, 2008). Functional MRI (fMRI) studies have identified the neural correlates of stimuli values not only in choice situations but also when subjects watch passively, give pleasantness ratings, or perform a distractive task (Hare et al, 2009;Lebreton et al, 2009;Levy et al, 2011). Brain regions whose activity correlates with subjective values are thought to compose a brain valuation system (BVS), which mainly includes the ventromedial prefrontal cortex (VMPFC) and the ventral striatum (VS), sometimes accompanied by limbic regions (Haber and Knutson, 2010;Peters and Buchel, 2010).…”
Section: Introductionmentioning
confidence: 99%